g_*^*-I-Closed Sets and Their Properties in in Ideal Topological Space - Rughzai Mahamood; Darwesh Mohammed (المجلة العراقية للعلوم الاحصائية, 2025)
There are many research papers that deal with different types of generalized closed sets. Levine [4] introduced generalized closed (briefly, -closed) sets and studied their basic properties and Veera Kumar [5] introduced -closed sets in topological spaces. The purpose of this present paper is to define a new class of generalized idea closed sets called -closed sets by using -open set .In this paper, we introduce the -closed sets, characterizations and properties of -closed sets and its complement and other related sets. We prove that the class of  closed sets lies between the class of -closed sets and the class of        -closed sets. Also, we find some relations between -closed sets and already existing closed sets. -open neighborhood is introduced and their properties are investigated.